Do Carbon Offsets Offset Carbon? - Raphael Calel; Jonathan Colmer; Antoine Dechezleprêtre; Matthieu Glachant (Center for Economic Studies and ifo Institute (CESifo), 2021)
We develop and implement a new method for identifying wasted subsidies, and use it to provide systematic evidence on the misallocation of carbon offsets in the Clean Development Mechanism—the world's largest carbon offset program. Using newly constructed data on the locations and characteristics of 1,350 wind farms in India—a context where it was believed, ex ante, that the Clean Development Mechanism could significantly increase development above baseline projections—we estimate that at least 52% of approved carbon offsets were allocated to projects that would very likely have been built anyway. In addition to wasting scarce resources, we estimate that the sale of these offsets to regulated polluters has substantially increased global carbon dioxide emissions.
Keywords: H23; H43; L94; Q42; Q54; 330; carbon offsets; infra-marginal support; subsidies; investment; wind power; misallocation